Histopathological Insights on Imaging Results of Intraoperative Magnetic Resonance Imaging, 5-Aminolevulinic Acid, and Intraoperative Ultrasound in Glioblastoma Surgery. Issue 1 (14th February 2017) - Coburger, Jan; Scheuerle, Angelika; Pala, Andrej; Thal, Dietmar; Wirtz, Christian Rainer; König, Ralph
Abstract: BACKGROUND: For appropriate use of available intraoperative imaging techniques in glioblastoma (GB) surgery, it is crucial to know the potential of the respective techniques in tumor detection. OBJECTIVE: To assess histopathological basis of imaging results of intraoperative magnetic resonance imaging (iMRI), 5-aminolevulinic acid (5-ALA), and linear array intraoperative ultrasound (lioUS). METHODS: We prospectively compared the imaging findings of iMRI, 5-ALA, and lioUS at 99 intraoperative biopsy sites in 33 GB patients during resection control. Histological classification of specimens, tumor load, presence of necrosis, presence of vascular malformations, and O6-methylguanin-DNA methyltransferase (MGMT) promoter state was correlated with imaging findings. RESULTS: Solid tumor was found in 57%, infiltration zone in 42%, and no tumor in 1% of specimens. However, imaging was negative in iMRI in 49%, using 5-ALA in 17%, and in lioUS in 21%. In positive imaging results, share of solid tumor was highest in 5-ALA (65%) followed by lioUS (60%) and lowest in iMRI (55%). In comparison to 5-ALA, iMRI had a high share of solid tumor in specimens when showing intermediate results. Sensitivity for invasive tumor was higher in 5-ALA (84%) and lioUS (80%) than in iMRI (50%). We found a significant correlation of 5-ALA with classification of specimen, presence of necrosis, and microproliferations. Methylated MGMT promoter correlated with positive findings in 5-ALA. lioUS and iMRI showed no correlations with histopathological findings. CONCLUSION: All of the assessed established imaging techniques detect infiltrating tumor only to a certain extent. Only 5-ALA showed a significant correlation with histopathological findings. Interestingly, tumor remnants in an MGMT-methylated tumor are more likely to be visible using 5-ALA as in unmethylated tumors.